Comunicação e Informação: v. 17, n. 2 (2014) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2015)
Link de acesso ao Número: http://www.revistas.ufg.br/index.php/ci/issue/current/showToc